2004
DOI: 10.1080/07315724.2004.10719367
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Deficiencies as Predisposing Factors for Hypertension in Lacto-Vegetarian Indian Adults

Abstract: Low dietary intakes of vitamin C, folic acid and zinc emerged as the possible risk factors for hypertension. Further, lower levels of plasma vitamin C, erythrocyte membrane zinc and ceruloplasmin were found to be the putative intermediary biomarkers in pathogenesis of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…Moreover, Chiplonkar et al showed that zinc intake and erythrocyte membrane-zinc were negatively correlated with blood pressure in a traditional Indian lacto-vegetarian population with a great risk of developing mild zinc deficiency (Chiplonkar et al, 2004). However, Sato et al found that severe zinc deficiency during adult life does not change blood pressure in normotensive rats (Sato et al, 2003), but it can aggravate hypertension in spontaneously hypertensive rats (Sato et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Chiplonkar et al showed that zinc intake and erythrocyte membrane-zinc were negatively correlated with blood pressure in a traditional Indian lacto-vegetarian population with a great risk of developing mild zinc deficiency (Chiplonkar et al, 2004). However, Sato et al found that severe zinc deficiency during adult life does not change blood pressure in normotensive rats (Sato et al, 2003), but it can aggravate hypertension in spontaneously hypertensive rats (Sato et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Data on habitual physical activity were collected using a validated structured questionnaire [16]. Information about duration in minutes of major daily activities such as sleep, sitting, standing, walking, exercise, recreation, and occupational activity were used to classify an individual into level of physical activity groups: inactivity, light and moderate activity [17].…”
Section: Physical Activity Assessmentmentioning
confidence: 99%
“…23 As deficiências de micronutrientes, muitas vezes observadas em lactovegetarianos, têm sido identificadas como fatores predisponentes à HAS em adultos seguidores desse estilo alimentar. 24 Fato relevante é a observação de que os vegetarianos apresentam, em geral, menor IMC, fato que, independentemente do tipo de dieta, se associa a menor PA. [25][26][27] Dieta vegetariana para hipertensos: grau de recomendação IIa; nível de evidência B.…”
Section: Tras)unclassified